Targeted Distraction: Spinal Growth in Children With Early-Onset Scoliosis Treated With a Tail-gating Technique for Magnetically Controlled Growing Rods. Issue 20 (15th October 2018) - Mardare, Mihai; Kieser, David Christopher; Ahmad, Adil; Subramanian, Thejasvi; Haleem, Shahnawaz; Thakar, Chrishan; Wilson-MacDonald, James; Nnadi, Colin
Abstract : Study Design: Prospective cohort study Objective: To understand the efficacy of a tail-gating technique (TGT) to mirror the normal spinal growth of children with early-onset scoliosis (EOS) treated with magnetically controlled growing rods (MCGR). Summary of Background Data: MCGR allow outpatient distraction and guided spinal growth without the need for repeat surgery. Two techniques (maximal and targeted) are currently employed to determine the distraction amount, however the efficacy of each is unknown. This study specifically assesses the ability of targeted distraction to achieve physiological growth. Methods: We performed a retrospective review of European children treated with MCGR using a TGT and analyzed the post-operative clinical and radiographic outcomes, including the sitting height, standing height, coronal Cobb angle, T1-T12 and T1-S1 height. Furthermore, we compared the post-operative sitting/standing height ratio every 6 months to those reported for normal age- and sex-matched European children. Results: Thirty-five children were included with a mean follow-up of 3.4 years (1.8–5.8 years). All clinical and radiographic parameters significantly ( P  < 0.05) improved immediately post-operatively and were maintained until final follow-up. The TGT mirrored the normative sitting/standing height ratios for expected spinal growth (Pearson correlation 0.95 for males and 0.90 for females). The mean difference between the reference values for the sitting/standing height ratio and our results was 0.0124 ( P  < 0.001) for males and 0.0068 ( P  = 0.010) for females. Conclusion: MCGR can reliably improve the coronal deformity in children with EOS while maintaining spinal growth. A TGT to determine the distraction amount at follow-up accurately mirrors the normal growth pattern of age-, sex-, and ethnicity-matched children. However, patients treated with this technique have a statistically significant, but clinically insignificant, shorter than physiologically normal spinal height. Level of Evidence: 3